Refining Policy with the Poor : Local Consultations on the Draft Comprehensive Poverty Reduction and Growth Strategy in Vietnam - Shanks, Edwin (World Bank, Washington, DC, 2014)
In March 2001, the Government of Vietnam produced an Interim Poverty Reduction Strategy Paper (I-PRSP), and announced its intention to develop a Comprehensive Poverty Reduction Strategy Paper (CPRGS) by the end of April 2002. In the I-PRSP, the Government outlined its commitment to involve a broad range of stakeholders - including poor communities, local government authorities, and the enterprise sector - in drafting the CPRGS. The Ministry of Planning and Investment, who was assigned by the Government of Vietnam to lead the CPRGS drafting process, asked the World Bank, and a group of international nongovernmental organizations to support them in carrying out the local consultations. The consultations took place in six rural, and urban locations across Vietnam, selected to represent a range of poverty situations. About 1,800 people participated in the research. This report, which is the first of three volumes documenting the local consultations, provides an account and reflection on the approach, and methodology used in the consultations. It is intended this may give useful practical experience for future monitoring of the CPRGS, as well as for people who are planning to carry out similar exercises in other countries. The report outlines the process that was followed from the point of developing a research outline from the I-PRSP, through the fieldwork exercises, data compilation, and analysis, leading on to identification of the main policy messages made by the participants. It also describes how the findings were used to influence the final version of the CPRGS.